Altered enhancer-promoter interaction leads to MNX1 expression in pediatric acute myeloid leukemia with t(7;12)(q36;p13) - Weichenhan, Dieter; Riedel, Anna; Sollier, Etienne; Toprak, Umut; Hey, Joschka; Breuer, Kersten; Wierzbińska, Justyna Anna; Touzart, Aurore; Lutsik, Pavlo; Bähr, Marion; Östlund, Anders; Nilsson, Tina; et al. (Blood advances, 2024)
Acute myeloid leukemia (AML) with the t(7;12)(q36;p13) translocation occurs only in very young children and has a poor clinical outcome. The expected oncofusion between break point partners (motor neuron and pancreas homeobox 1 [MNX1] and ETS variant transcription factor 6 [ETV6]) has only been reported in a subset of cases. However, a universal feature is the strong transcript and protein expression of MNX1, a homeobox transcription factor that is normally not expressed in hematopoietic cells. Here, we map the translocation break points on chromosomes 7 and 12 in affected patients to a region proximal to MNX1 and either introns 1 or 2 of ETV6. The frequency of MNX1 overexpression in pediatric AML is 2.4% and occurs predominantly in t(7;12)(q36;p13) AML. Chromatin interaction assays in a t(7;12)(q36;p13) induced pluripotent stem cell line model unravel an enhancer-hijacking event that explains MNX1 overexpression in hematopoietic cells. Our data suggest that enhancer hijacking may be a more widespread consequence of translocations in which no oncofusion product was identified, including t(1;3) or t(4;12) AML.